Interaction of telmisartan and related sartans with the programmed cell death-ligand 1 (PD-L1) protein dimer: a molecular docking analysis - Gérard Vergoten; Christian Bailly (SpringerOpen, 2023)
Abstract Background Telmisartan (TLT) is a prototypic angiotensin receptor blocker largely used to treat hypertension worldwide. In addition to its cardioprotective effects, TLT presents pleiotropic activities and notably displays noticeable anti-inflammatory and antitumor effects. The repression of the programmed cell death-1 (PD-1)/programmed death-ligand 1 (PD-L1) immune checkpoint may be implicated antitumor action of TLT, as it is the case with many other compounds equipped with a biphenyl moiety. We have used molecular modeling to compare the interaction of TLT and derivatives with the PD-L1 dimer protein. Results Two molecules, TLT-dimer and TLT-acylglucuronide, were found to form more stable complexes with PD-L1 than TLT itself. In parallel, the docking analysis performed with a series of 12 sartans led to the identification of Olmesartan as a potential PD-L1 binder. The stacked biphenyl unit of Olmesartan positions the molecule along the groove delimited by the two protein monomers. The flanking tetrazole and imidazole moieties, on each side of the biphenyl unit of Olmesartan, contribute favorably to the protein interaction via specific hydrogen bonding interactions. Conclusions The computational analysis suggests a possible binding of Olmesartan to PD-L1 dimer and thus offers novel perspectives for the design of small molecules capable of interrupting the PD-1/PD-L1 immune checkpoint. Experimental studies are warranted to validate the hypothesis. Graphical abstract